Transesterification of Canola Oil with Methanol using Nano Zinc Oxide Supported Catalysts - Boz, Nezahat (Asian Journal of Chemistry, 2015)
Nano zinc oxide supported catalysts were prepared by an impregnation method with an aqueous solution of K2CO3 (3-10 wt. %) and tested for the transesterification of canola oil with methanol. Several operating variables were used in order to assess their influence on the methyl ester yield, namely, the weight ratio of K2CO3 over ZnO (3-10 %), the reactant feed ratio (alcohol/oil: 6/1-18/1), the reactor temperature (298, 318, 333 and 338 K), reaction time (1-9 h) and the catalyst concentration (varied between 1-7 wt. %). 10 wt. % K2CO3 impregnated on nano particles of zinc oxide were found to be the active catalysts resulting in high conversion of 97.83 ± 1.82 % for transesterification of canola oil at 338 K with methanol/oil ratio of 9/1 and using 5 wt. % catalysts.